Analisis Sistem S-Commerce Sebagai Bussiness Process Management Pada Tiktok Shop (Studi UMKM di Indonesia Dengan Pendekatan SOAR) - Maharani Ulya Fadhilah; Jeni Susyanti (PT PUBLIKASI INSPIRASI INDONESIA, 2024)
This research is motivated by the phenomenon of the emergence of Tiktok Shop as s-commerce which has a huge influence on economic growth in Indonesia, especially for MSME players in the current digital era. The focus of this research uses the competitiveness framework from Stavros, Cooperrider, & Kelly to describe Tiktok Shop's strength map in digital transformation through SOAR analysis. The research method used is a systematic literature review with a meta-synthesis approach. The results showed that Tiktok Shop has offered significant opportunities for MSMEs in Indonesia to take advantage of digital transformation in developing businesses. However, there are several challenges that need to be overcome, including intense competition, building trust and credibility with consumers, reaching the right audience, and issues related to user data privacy and security. Collaborative efforts with various parties show strategic steps to support the growth of MSMEs in the Tiktok Shop ecosystem as a C2B model with an innovative approach and focus on user experience so that it has the potential to become a major player in the s-commerce industry.